Peranan Orang Tua Dalam Pengembangan Literasi Dini Selama Covid-19 Pada Anak Usia 5-6 Tahun - Fitri Annisa; Delfi Eliza (Cakrawala: Jurnal Pendidikan, 2021)
This study aims to reveal the role of parents in developing children's early literacy during the Covid-19 period, by using a survey method with 26 respondents, namely parents of 13 boys and 13 girls. The analysis was carried out using the percent index formula and SPSS 16 software. The instrument was validated with expert judgment techniques and the reliable test showed the number 0.912> 0.60, which means that the questionnaire was reliable. The results of the data analysis showed that the parents in the TK Pembangunan Laboratorium UNP were in the category of less role, with the average percentage of all skills being 62.09%. Researchers have revealed the role of parents in developing children's early literacy with details of the ability to print motivation skills of 53.34% which means less, print motivation skills of 67.04% which means sufficient, phonological awareness skills of 70.68% which means sufficient, vocabulary skills of 67.21% which means enough, narrative skill is 60.74% which means less, and letter knowledge is 53.55% which means less.